Pierre August Renoir - Venezia, Mike. (New York : Children's Press, 1996)
Briefly recounts the role of Renoir, along with his fellow artists, in the development of a new type of painting known as Impressionism.
Booklist.
Elem. School Library Collection.
School Library Journal.
5.5
K-3
Keywords: Renoir, Auguste, -- 1841-1919 -- Juvenile literature; Renoir, Auguste, -- 1841-1919.; Renoir, Auguste, -- 1841-1919.; Painting -- Appreciation -- Juvenile literature; Artists; Impressionism (Art); Painting, French; Artists -- France -- Biography; French painting; Impressionism (Art)